2019
DOI: 10.3390/molecules24091739
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of KDM5 Histone Demethylases Increase the Radiosensitivity of Breast Cancer Cells Overexpressing JARID1B

Abstract: Background: KDM5 enzymes are H3K4 specific histone demethylases involved in transcriptional regulation and DNA repair. These proteins are overexpressed in different kinds of cancer, including breast, prostate and bladder carcinomas, with positive effects on cancer proliferation and chemoresistance. For these reasons, these enzymes are potential therapeutic targets. Methods: In the present study, we analyzed the effects of three different inhibitors of KDM5 enzymes in MCF-7 breast cancer cells over-expressing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…Knockdown of these proteins decreases the ability of cells to repair their damaged DNA (25)(26)(27). Similarly, small molecule inhibitors of KDM5 enzymes increase the levels of H3K4me3 chromatin modification which in turn leads to impaired DNA repair through both homologous recombination and non-homologous end joining (28,51). Our data are in agreement with these observations.…”
Section: Discussionsupporting
confidence: 89%
“…Knockdown of these proteins decreases the ability of cells to repair their damaged DNA (25)(26)(27). Similarly, small molecule inhibitors of KDM5 enzymes increase the levels of H3K4me3 chromatin modification which in turn leads to impaired DNA repair through both homologous recombination and non-homologous end joining (28,51). Our data are in agreement with these observations.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, specific inhibitory drugs have been developed and are currently in pre-clinical trials, including EPT103182, a KDM5 inhibitor in hematological cancers, such as multiple myeloma, and GSK-J1, a KDM6 inhibitor, in glioma, both with high efficacy against cancer cells [97,99] (Table 1). RS compounds were suggested to increase breast cancer cells sensitivity to RT, affecting DNA repair mechanisms [100] (Table 1). Additionally, KDM6 subfamily inhibitors, such as GSK-J1/J4, also enhanced glioblastoma cells radiosensitivity, as well as, in breast and lung adenocarcinoma cell lines [99] (Table 1).…”
Section: Emerging Novel Therapeutic Targets Through Epigenetic Chrmentioning
confidence: 99%
“…Evidence is emerging that JARID1B contribute to the epigenetic plasticity that underlies malignant transformation [24]. Studies have also shown that JARID1B is an overexpression in numerous cancers [25], JARID1B overexpression is associated with a poor prognosis in breast and prostate cancers [26,27]. Having studies shown that histone demethylase JARID1B associated with CRC cells growth [28].…”
Section: Discussionmentioning
confidence: 99%